Teachers Understanding about Interesting Online Learning Media - Intan Nurma Yulita; Yeni Rizka (Institut Teknologi Nasional, Bandung, 2021)
Implementation of Indonesian Education in the New Normal Era after the global Covid-19 pandemic uses an online learning system in accordance with new policies and regulations from the government to break the chain of virus spread in the community. With this system, teachers and students are required to understand online learning media quickly. However, students feel bored with the online learning system because it tends to be monotonous and many tasks are given. In addition, teachers are not necessarily proficient in using these online learning facilities and media, especially to make online learning interesting so that students do not get bored. Therefore, a webinar was conducted to improve teacher’s understanding of interesting online learning media such as Kahoot, Mentimeter, and Quizizz. Based on the results of quantitative calculations through the participant’s pre and post-tests, the participant’s knowledge changes were 28% on Mentimeter, 23% on Kahoot, and 18% on Quizizz.